Routledge International Handbook of Contemporary Participatory Design
1 online resource (xxvi, 300 pages).
Keywords: This handbook offers a comprehensive overview of key themes and agendas in contemporary Participatory Design across diverse disciplines, continents, communities, and practices. Building on Participatory Design's core values of empowerment and democracy, the handbook explores how the field is developing and diversifying to address contemporary societal challenges in a global community. Participatory Design actively engages peoples, groups and other actors in collaborative design processes to explore and co-create their everyday technologies, practices, and environments. In doing so, Participatory Design aims to address social justice and agency by including diverse actors in the collective shaping of alternative futures. Participatory Design embraces a diverse collection of principles and practices aimed at making technologies, environments, organisations and institutions more responsive to human and planetary needs. In this volume, a multidisciplinary and international group of highly experienced and recognised experts present an authoritative review of the contemporary field and discuss the diverse opportunities and challenges that arise from pivotal issues in Participatory Design, including scaling, collectives, sustainability and more-than-human, decolonisation, emerging technologies and AI, new approaches, methods and engagement beyond academia. The handbook advances contemporary research, theory and practice and highlights case studies that demonstrate how Participatory Design can bring about game-changing shifts in diverse contexts. The volume is an invaluable resource for students, researchers, scholars, and professionals who seek to utilise Participatory Design research and practice to enrich, support and transform complex contemporary conditions towards inclusive, sustainable and transitional futures.